ANALISIS KETERSEDIAAN AIR PADA PERTANIAN LAHAN KERING DI GUNUNGKUDUL YOGYAKARTA - Farik Khalimi; Zaenal Kusuma (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2018)
The development of agriculture in dry land, is expected to contribute in the field of Indonesian agriculture. Dry land agriculture has some problem i.e. the low moisture content and drought. The drought that occurred in Gunungkidul, one of them. The purpose of this research was to evaluate the availability of water on some of the land use in each soil depth by using two approaches, namely evaluation of the evapotranspirasi and the characteristics of land, with the intend to present information about the relationship of some land use with the availability of water in dry land farming in Gunungkidul. Models were used to calculate evaporanspirasi and crop water needs, calculate the physical properties of the soil, and comparing the two calculations. The results of the analysis indicated that the availability of water in dry land farming in Gunungkidul Yogyakarta was influenced by the characteristics of the land (physical properties of the soil) 21,5% and the remainder was by other factors. The highest available water was on sugar cane plantation, 42,81% in 0-20 cm depth. The available water on forest land and teak product was 35,68% in 40-60 cm depth.